Penerapan Model Discovery Learning Berbantuan Google Document untuk Meningkatkan Keterampilan Berpikir Kritis dan Kolaboratif - Haryani Haryani (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims to describe using Google Document-assisted Discovery Learning and to find out the improvement critical thinking skills and collaboration in Derivative Algebraic Functions material for the 2020/2021 academic year. The research subjects were 36 students in class XI IPA 4 at SMA N 1 Yogyakarta. The study was divided into two cycles of two meetings each. Each process is divided into four stages: planning, execution, observation, and reflection. Critical thinking and collaboration skills are assessed using observation sheets and questionnaires distributed at the second cycle meeting. The results demonstrate that applying the Google Document-assisted Discovery Learning model to Algebraic Function Derivative material can enhance the students' thinking and collaboration skills. Critical thinking skills increased from 85.65% in cycle 1 to 89.35% in cycle 2 with the essential category, while collaboration skills increased from 85.45% in cycle 1 to 90.58% in cycle 2 with the very collaborative category.